Training program evaluation for educational supervisors: Selected training programs in the headquarters of the ministry of education, sultanate of Oman / Zayid Ali Khalfan Al-Hosni - Al-Hosni, Zayid Ali Khalfan (2014)

(untitled)
Training is one of the major components of human resource development, but training is incomplete unless evaluation has taken place. Hence, this research aims to investigate the current practices in evaluating the training programs of educational supervisors (ES) carried out by the Ministry of Education (MOE) in Oman. The objectives of the current study are: (1) to explore the participants’ perceptions regarding the practice in evaluating the training programs for educational supervisors by the MOE in Oman, (2) to identify the similarities and differences among the participants in their perceptions concerning the evaluation of the training programs, and (3) to identify some ways to help the MOE in Oman in improving the evaluation of the training programs. This research has adopted a qualitative approach in collecting data, whereby semi-structured interviews were used as the main source, supplemented by direct observations and document analysis. The researcher has used a purposeful site and training program selection. This study has gathered data from three selected training programs held centrally in the MOE headquarters within the year 2011, official training programs plan. The participants selected were trainers, trainees, training evaluators, training providers, and superiors. The validity and reliability of the current study were established through adequate engagement, in-depth observation and triangulation. A multiple case study design method and cross-site analysis were used in this research. Findings showed that the current aims of evaluation focused more on short-term rather than long-term impacts of the training. Results showed that the existing process of the evaluation was mostly done at random inconsistent timing, took a longer time and incurred high cost. There were many similarities and differences in the current practices and levels of evaluation. To improve the present training evaluation, iii interviewees recommended: (1) activating the school administration in carrying out the evaluation, (2) applying a practical approach in evaluating such as using the internet, establishing an independent training evaluation centre, and (3) enhancing the qualification of evaluators by providing specialist training in evaluation, and extending the capacity of the administration. This research has been concluded with recommendations for new components of evaluation framework that can be applied by the stakeholders in MOE of Oman in implementing the evaluation of the training programs.